The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1091/mbc.e13-08-0471
|View full text |Cite
|
Sign up to set email alerts
|

Kdm3a lysine demethylase is an Hsp90 client required for cytoskeletal rearrangements during spermatogenesis

Abstract: Chromatin remodeling enzymes can also have nonhistone roles, broadening their biological functions. It is shown that Kdm3a binding to cellular chaperones in the cytoplasm is relevant for morphogenetic events leading to infertility in enzymatically null mice. This provides evidence that Kdm3a is not just a histone modifier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 63 publications
(59 reference statements)
3
35
0
Order By: Relevance
“…Interestingly, mouse mutants for the histone N-lysine demethylase Kdm3a (Jmjd1a, Tsga, or Jhdm2a) are obese, predisposed to diabetes (Inagaki et al, 2009;Tateishi et al, 2009), and have male infertility phenotypes (Okada et al, 2007) overlapping with mouse models of dysfunctional cilia. Structural abnormalities of the acrosome and manchette were observed in mutant Kdm3a mouse spermatids (Kasioulis et al, 2014) similar to those reported for conditional inactivation of Ift88 (Kierszenbaum, 2002;San Agustin et al, 2015). KDM3A localizes to the actin-rich acrosome-acroplaxome region, which is altered in Kdm3a mutant spermatids (Kasioulis et al, 2014).…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…Interestingly, mouse mutants for the histone N-lysine demethylase Kdm3a (Jmjd1a, Tsga, or Jhdm2a) are obese, predisposed to diabetes (Inagaki et al, 2009;Tateishi et al, 2009), and have male infertility phenotypes (Okada et al, 2007) overlapping with mouse models of dysfunctional cilia. Structural abnormalities of the acrosome and manchette were observed in mutant Kdm3a mouse spermatids (Kasioulis et al, 2014) similar to those reported for conditional inactivation of Ift88 (Kierszenbaum, 2002;San Agustin et al, 2015). KDM3A localizes to the actin-rich acrosome-acroplaxome region, which is altered in Kdm3a mutant spermatids (Kasioulis et al, 2014).…”
Section: Introductionsupporting
confidence: 80%
“…Structural abnormalities of the acrosome and manchette were observed in mutant Kdm3a mouse spermatids (Kasioulis et al, 2014) similar to those reported for conditional inactivation of Ift88 (Kierszenbaum, 2002;San Agustin et al, 2015). KDM3A localizes to the actin-rich acrosome-acroplaxome region, which is altered in Kdm3a mutant spermatids (Kasioulis et al, 2014). In spite of these phenotypic and functional overlaps, a link between KDM3A and ciliogenesis has not been investigated.…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…Some effects of HSP90 on the cytoskeleton may be mediated by other proteins like the lysine demethylase Kdm3a. Mutant Kdm3a mice display male infertility and their cells show an altered fractionation of actin and tubulin (Kasioulis et al 2014). …”
Section: Role In Molecular Evolutionmentioning
confidence: 99%
“…KDM3A is also involved in other cellular processes such as cell cycle, embryonic and adult stem cell renewal, and differentiation of vascular smooth muscle (15). KDM3A has been implicated in the development and progression of several malignancies, including hepatocellular carcinoma and gastric cancer (16, 17).…”
Section: Histone Demethylases and Rccmentioning
confidence: 99%